Antibiotic prescribing for children in primary care and adherence to treatment guidelines. (5th March 2016) - Ivanovska, Verica; Hek, Karin; Mantel Teeuwisse, Aukje K.; Leufkens, Hubert G. M.; Nielen, Mark M. J.; van Dijk, Liset
Abstract: Objectives: Antibiotic use is unnecessarily high for paediatric respiratory tract infections (RTIs) in primary care, and implementation of treatment guidelines is difficult in practice. This study aims to assess guideline adherence to antibiotic prescribing for RTIs in children and examine potential variations across Dutch general practices. Methods: We conducted a retrospective observational study, deriving data on diagnoses and prescriptions from the electronic health records-based NIVEL Primary Care Database. Patients <18 years of age with a diagnosis of fever, ear and respiratory infections (International Classification of Primary Care codes A03, H71, R72, R75, R76, R78 and R81) during 2010–12 were included. Antibiotics were linked to episodes of illness. Two types of disease-specific outcomes were used to assess adherence to national guidelines regarding antibiotic prescribing choices. Inter-practice variability in adherence was assessed with multilevel analysis. Results: Half of the episodes with RTIs with restrictive prescribing policy and 65% of episodes with pneumonia were treated with antibiotics. General practitioners prescribed antibiotics for 40% of episodes with bronchitis, even though guidelines discourage antibiotic prescribing. First-choice antibiotics were prescribed in 50%–85% of episodes with selected diseases, with lowest values for narrow-spectrum penicillins. Levels of adherence to guidelines varied widely between diagnoses and between practices. Conclusions: Most paediatric RTIs in the Netherlands continue to be treated with antibiotics conservatively. Potential aspects of concern are the inappropriate antibiotic prescribing for acute bronchitis and the underuse of some first-choice antibiotics. Continuing progress may be achieved by targeting practices with lower adherence rates to guidelines.